2012
DOI: 10.2478/v10131-012-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

An Interaction between Exercise Order and Rest Interval during Lower-Body Resistance Exercise

Abstract: Background:The purpose of the present study was to compare the influence of two-and five-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The obtained regression models make it possible to calculate the number of repetitions and rest interval to achieve the most rational load variant. These data supplement the results presented in the studies by Iermakov, Ivashchenko, Khudolii, and Chernenko (2020), Ivashchenko, Khudolii, Prusik, and Giovanis (2020) and form a methodology for studying training loads, which differs from the methods used in the studies by Arazi et al (2012), Ratamess et al (2012), Miranda et al (2010) in that research is conducted using an active 2 k FFE and materials are processed with the help of regression and discriminant analysis.…”
Section: Regression Equationssupporting
confidence: 51%
“…The obtained regression models make it possible to calculate the number of repetitions and rest interval to achieve the most rational load variant. These data supplement the results presented in the studies by Iermakov, Ivashchenko, Khudolii, and Chernenko (2020), Ivashchenko, Khudolii, Prusik, and Giovanis (2020) and form a methodology for studying training loads, which differs from the methods used in the studies by Arazi et al (2012), Ratamess et al (2012), Miranda et al (2010) in that research is conducted using an active 2 k FFE and materials are processed with the help of regression and discriminant analysis.…”
Section: Regression Equationssupporting
confidence: 51%
“…In contrast to Arazi, et al (2012), Ratamess, et al (2012), Miranda, et al (2010, the study obtained data on the impact of orthogonal variants of alternation of strength exercises and rest intervals on the training effect of strength training loads. The paper confirmed that the efficiency of discriminant analysis increases when using 2 k FFE active experiments (Neimark, & Teklina, 2012;Tort-Martorell, 2009, 2012;.…”
Section: Discussionmentioning
confidence: 99%
“…The effective use of loads in physical education goes hand in hand with control and targeted regulation of rest intervals between exercises, their repetition and training in general, as well as with management of training effects of exercises (Ivashchenko, 2016;Bosenko, 2016;Veremeenko, 2019). The importance of studying rest intervals between strength exercises is indicated in papers by Arazi, Mirzaei, Sangdevini, and Abadi (2012), Ratamess, Chiarello, Sacco, Hoffman, Faigenbaum, Ross, and Kang (2012), Miranda, Simão, DosSantos-Vigário, DeSalles, Pacheco, and Willardson (2010). ISSN 1993-7989 (print).…”
Section: Introductionmentioning
confidence: 99%
“…Although our results provide some elements for the development of such criteria" [7]. On the other hand Arazi, H., et al states in his research conclusion that "The ability to maintain repetitions and to perform a higher volume of training has been shown to be essential for stimulating greater strength and hypertrophy adaptations" [8].…”
Section: Resultsmentioning
confidence: 58%